Music, arts and intercultural education: the artistic sensibility in the discovery of the other - Maria do Rosário Sousa (Journal of Science and Technology of the Arts, 2011)
The present article presents a doctoral investigation. It mainly focuses on an action research whose problematic is based on the search for didactic-pedagogical paths which contribute to intercultural openness and change within schools allowing for better social integration. We have chosen the trilogy music, arts education and interculturality to address the central problematics of this research. Therefore an Intercultural Musical Program was conceived, implemented and assessed in three Portuguese Elementary/Preparatory schools. The main leading forces guiding this Program are attached to four areas, which constitute the theoretical/conceptual frame of this research: Artistic education as a priority in education; • Intercultural education as a response to a growing cultural diversity; The role of music as an harnessing methodology for intercultural communication; Arts Programs as globalising impulses for human development and the preservation of cultural heritage. The empirical work rests on a methodology of qualitative analysis based on Renald Legendre’s (1993, 2005) model of Pedagogical Relationship (PR), combined with a strong influence of Visual Anthropology. The attained results are indicators of the high relevance and participation, as well as of the transforming impact of this action research, as a facilitator of intercultural communication and education among communities.